Battlestar Galactica (1978) [videorecording (DVD)] - Dykstra, John, 1947-; Larson, Glen A.; Colla, Richard A.; Levi, Alan J.; Hatch, Richard, 1945-2017; Benedict, Dirk; Greene, Lorne; Jefferson, Herb, Jr., 1946-; Jensen, Maren, 1957-; Swartz, Tony, 1943-; Hathaway, Noah, 1971-; Carter, Terry, 1928-; et al. (Universal, 2003)
In the deepest reaches of space, the fight to save all human life from extinction has begun. Hoping for lasting peace following centuries of intense warfare, the Twelve Colonies gather to sign a treaty with their dreaded enemies, the Cylons. But after an act of treachery, the Cylons launch a devasting surprise attack, destroying the Colonies home planet. A lone flagship, the Galactica, remains to aid the surviving colonists on their epic journey to their new home - far-off Earth.